Pedagogical consciousness and its value in the system of additional education - Ushkalova A. I., Skorobogatko M. M., Voronova T. M. (Development of modern education system: theory, methodology, experience, 2019)
The article considers the pedagogical consciousness of the teacher, as an indicator that largely determines his desire to build a learning process. Pedagogical consciousness is represented as a system in the unity of the educational space. The forms of pedagogical consciousness and their influence on the pedagogical reality are analyzed.
Keywords: учебный процесс; методы обучения; дополнительное образование; знания; educational process; образовательное пространство; knowledge; teaching methods; educational space; pedagogical consciousness; additional education; pedagogical reality; students' creative abilities; social needs of society; педагогическое сознание; педагогическая действительность; творческие способности учащихся; социальные потребности общества